Cyber-physical systems as a platform for value co-creation : case: intelligent equipment in mining and construction industry - Hänninen, Johanna (2014)
This thesis focuses on value co-creation in the context of Cyber-Physical Systems (CPSs) in a networked business environment. The object is to investigate how value is co-created in one particular networked environment, in the min-ing and construction industry, where the intelligent equipment are examples of CPSs. The research is interpretive case study, including one case company, which is a global organization preparing tools and equipment for the mining and construction industry. The framework for value co-creation in Consumer Information Systems (CIS) is used as a framework for value co-creation to study how the different actors from the case company and their customers (=20) per-ceive value co-creation and what are the system value propositions enabling the value co-creation and the value drivers driving the actors to co-create value in the context of intelligent equipment. The data collection was done using the laddering technique and for the analysis a thematic approach was adopted to turn the data into meaningful graphical presentations.